The portrayal of technology and propaganda through the lens of World War II films - Lim, Yan Quan (Nanyang Technological University, 2022)
As World War II started to break out in the different countries, film acted as one of the biggest mediums that governments utilized to spread their ideologies and beliefs to the common people. Technology was a big player during World War II as they determined the course that each country was taking and became the tool for success or failure for each individual nation. As nations started to portray technology in their own films, technology also became a way for the government to glorify its own military as well as to attract people to serve the nation in their own ways. Many technologies were developed and focused upon during this time, however, since this was during the war, much of the main technology that was portrayed and glorified in films were military technologies. This paper hence aims to understand how certain technologies have been improved or researched upon and argues that films which portray technology during WWII acted as a tool for the government to spread propagandic materials and ideologies.